INNOVATIVE TEACHING OF ENGLISH IDIOMATIC EXPRESSIONS FOR EFL LEARNERS - Asri, Atiqah Nurul; Rochmawati, Dyah (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
Idioms are an important part of acquiring a language and oftenindicate proficient learner. English idioms are a part of the culturalelements of the language which should be mastered by EFL learners. Bydeveloping a clear understanding of figurative language, such as idiomaticexpressions, students can further comprehend texts that containmetaphorical and lexical meanings beyond the basic word level. However,learners with cultural literacy and language weakness are often challengedby idioms. There are several different ways to improve learners‘ idiomcomprehension. The present article investigates what types of innovativeteaching approaches and methods can be used when teaching idiomaticexpressions to learners of English. It suggests that idioms need to belearned so increasing the learners‘ awareness of these unique words andphrases can help them learn to identify and interpret them with greatersuccess.